Membangun Mindset Kewirausahaan Mahasiswa: Tinjauan Literatur Sistematis Terhadap Karakteristik, Peran, dan Ciri Kewirausahaan - Edo Permata; Jhon Veri (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to systematically analyze the literature related to the development of students’ entrepreneurial mindset over the past five years (2019–2024). The research method used is a Systematic Literature Review (SLR) following the PRISMA 2020 protocol, supported by visual analysis using VOSviewer. Data sources were obtained from reputable academic databases such as Google Scholar, Scopus, and ScienceDirect. Data collection was carried out by searching for relevant articles using specific keywords aligned with the research topic. Out of 1,245 identified articles, 146 met the inclusion criteria and were selected for further evaluation. Data analysis was conducted using a thematic-descriptive approach by categorizing key findings into several main themes. The results indicate that the formation of students’ entrepreneurial mindset is strongly influenced by experiential learning, institutional support from higher education, and psychological factors such as self-confidence, creativity, and tolerance for failure. Three main clusters emerged from the thematic mapping: (1) cognitive and psychological aspects, (2) the role of lecturers and curriculum, and (3) student entrepreneurial behavior. This study offers significant insights for the development of higher education policies to foster an innovative and resilient generation of young entrepreneurs through cross-sector collaboration.